Status Anak Yang Lahir Dari Kawin Lari Menurut Perspektif Hukum Islam dan Hukum Adat - Lilies Anisah (Justici, 2021)
Marriage is the beginning of living together in a bond that is regulated in laws and regulations with the intention of forming a happy family, as mandated by Article 1 of Law Number 1 of 1974 concerning Marriage, which reads: "The purpose of marriage is also to form a happy family. happy and eternal based on God Almighty". Because marriage/marriage aims to form a happy and eternal family (household), it means that in the household there should be a harmonious relationship between husband and wife and family members based on the principle of mutual respect (respect) well, calmly, peacefully and mutually love with growing affection, creating a peaceful home based on love. Elopement that is not followed by a guardian, then the marriage is void or can be canceled and the child born from the marriage is illegal according to Islam and can only inherit from the mother and her mother's family, but if the elopement child has fulfilled the legal requirements of the marriage mentioned in Article 42 Chapter IX of Law Number 1 of 1974 concerning Marriage, the child is a legitimate child. Meanwhile, when viewed from customary law a child born from an elopement has the same rights and position as a child born from an ordinary marriage, the position of the child Those born in elopement are legal children as long as the marriage is carried out in accordance with established procedures. If the procedure carried out is not in accordance with what has been determined, the child becomes an illegitimate child.